1985
DOI: 10.1111/j.1365-2141.1985.tb07418.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, in vivo redistribution and sites of sequestration of indium‐111‐labelled platelets in giant platelet syndromes

Abstract: Six patients with giant platelet syndrome were examined: four with Bernard-Soulier syndrome (two were asplenic); one with hereditary thrombopathic thrombocytopenia; and one with May-Hegglin anomaly. Autologous platelets were labelled with In-111-oxine and in vivo redistribution and sites of sequestration measured with quantitative imaging. In Bernard-Soulier syndrome platelet survival was normal or moderately shortened; platelet turnover was decreased only in the two patients with thrombocytopenia. In the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…A collection efficiency greater than 100% can be explained by mobilization of platelet from the spleen as an active response to withdrawal of platelets from circulating blood . About one‐third of body platelets are trapped in a healthy spleen, so as a result the number of collected platelets can be higher than expected . We think that the technical changes introduced in the procedure contributed to the significant increase in the collection's efficiency seen in our case.…”
Section: Discussionmentioning
confidence: 68%
“…A collection efficiency greater than 100% can be explained by mobilization of platelet from the spleen as an active response to withdrawal of platelets from circulating blood . About one‐third of body platelets are trapped in a healthy spleen, so as a result the number of collected platelets can be higher than expected . We think that the technical changes introduced in the procedure contributed to the significant increase in the collection's efficiency seen in our case.…”
Section: Discussionmentioning
confidence: 68%
“…Males had an over‐yield mean of 0.23 ± 0.59 × 10 11 PLTs ( n = 1143) while females had an over‐yield mean of 0.10 ± 0.57 × 10 11 PLTs ( n = 643). Heyns and colleagues have shown that two‐thirds of PLTs in normal persons remain in the circulation and the remainder one‐third is in an exchangeable pool in the spleen . Fontana et al went further to show that one‐third of PLTs collected in a single apheresis donation are recruited from the spleen .…”
Section: Discussionmentioning
confidence: 99%
“…While the defect of GPIbα‐VWF interaction explains the in vivo and in vitro functional defects of Bolzano platelets, the pathogenetic mechanisms linking the Ala156Val substitution to thrombocytopenia and platelet macrocytosis are still uncertain, although indirect evidence suggested that a defect of platelet formation may be involved [5–7]. The analysis of in vitro megakaryopoiesis in six heterozygous subjects reported in the present study supported this hypothesis, in that we have shown that in all patients, and independently from the origin of Mks (peripheral blood or cord blood stem cells), Mk differentiation and maturation was similar to controls, while PPF was severely reduced both in Mks grown in suspension and in cells adhering to VWF or fibrinogen.…”
Section: Discussionmentioning
confidence: 99%